THE GRANT-IN-AID SYSTEM FOR INTERSTATE HIGHWAY CONSTRUCTION: AN ACCOUNTING OR ECONOMIC PROBLEM? - Manes, Rene Pierre (The Accounting Review, 1964)
The article informs that few sectors of governmental endeavor have grown at the explosive rate in the U.S. and that has marked highway construction since 1956, date of a new and expanded Federal Aid Highway Act. Today the construction of Interstate highways constitutes the largest public works program in the history of the world. Despite this claim on public attention in general and on the interest of accountants in particular, there are several reasons why this work receives relatively little publicity, its budget is dwarfed by defense, space and agricultural subsidy outlays, the cost of highway construction is not recorded in any single total amount, being divided as it is, between Federal and State agencies. The extent of autonomy which has been left to each State for the fulfillment of its share of a national system must be gratifying even to the most ardent states rights advocate. And in fact, as could be expected, the individual States have gone forward with the job at widely variant rates of speed and with quite different degrees of efficiency, enthusiasm and integrity, some exceeding all plans for progress and others lagging far behind.